The Struggle for Symbolic Space: The Choice of the Patron-Spirit of the City of Kazan - Sergeev, Sergey; Sergeeva, Zulfia (International Journal of Criminology and Sociology, 2022)
In the article, the concept of “genius of a place” is defined as a historical or mythological character of particular importance for the locality, possible applicants for the role of “genius of a place” in Kazan are considered, the political and social mechanisms that determine the nomination of one or another applicant are identified. The authors suggest that the “genius of the place” of Kazan is not a certain static, formed, and integral image. The population of Kazan is heterogeneous, and the various groups of its constituents — the administrative and managerial elite and the intelligentsia, conservatives and liberals, Russians and Tatars — have their idea of what the “genius of the place” of Kazan should look like. Researchers come to the conclusion that the “genius of the place” is an embodied group sociocultural ideal, and the struggle and conflicts taking place in a symbolic form partly prevent the transformation of existing intergroup contradictions into real ethnosocial and ethnopolitical conflicts.